The Contradiction of the Presence of Jehovah’s Witnesess as Christian Denomination in Yogyakarta - Arifuddin Ismail (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
The Presence of Jehovah’s Witnesses which has contradictory concepts has harassed mostly Christian people, but it attracts many people to join this group. Even nowadays this denomination has a significant progress in number of population. This research is aimed to find the answer of the above problem and to describe about whether Jehovah’s Witnesses as a Christian denomination or religious sect in which its existence are opposed by Christian community in general. Subject of this research is focused on Jehovah’s Witnesses in Yogyakarta. This Christian denomination becomes an international religious movement and has been assured in the 1945 Constitution as well as gets recognition from the government as a religious organization who has equal rights. In Yogyakarta, this group is also accepted; this is a picture of Yogyakarta as a multicultural city, and a town with high tolerance. In contrast, other Christian’s denominations have rejected this sect because it has different basic theology. The emergence of new denominations is caused by the absence of limitation in this open room. Therefore, it needs a “re-thinking” whether to leave this phenomenon free or to create a rule to control this situation so as to create harmony in managing religious life.